2019
DOI: 10.1364/oe.27.000282
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional hexagonal boron nitride nanosheet as the planar-alignment agent in a liquid crystal-based electro-optic device

Abstract: The planar-alignment agent in an electro-optic liquid crystal (LC) device plays an essential role for the LC's electro-optical characteristics. Rubbed polyimide (PI) layers are conventionally used as the planar-alignment agent in traditional liquid crystal displays (LCDs). Here we experimentally demonstrate that the 2D hexagonal boron nitride (h-BN) nanosheet can serve as the planar-alignment agent in an LC cell. This h-BN has higher chemical stability and more optical transparency than the PI layer. Two h-BN-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 37 publications
1
18
1
Order By: Relevance
“…Therefore, the hexagonal benzene rings in the LC and the hexagonal 2D h-BN lattice structure have almost the same size. It has been experimentally shown that this nano-architectural symmetry of the hexagons in these two species leads the benzene rings of the LC to coherently align on the hexagonal lattice of h-BN [12]. This epitaxial interaction is schematically presented in Figure 1a by matching the LC benzene rings on the hexagons of the h-BN lattice.…”
Section: Methodsmentioning
confidence: 94%
See 2 more Smart Citations
“…Therefore, the hexagonal benzene rings in the LC and the hexagonal 2D h-BN lattice structure have almost the same size. It has been experimentally shown that this nano-architectural symmetry of the hexagons in these two species leads the benzene rings of the LC to coherently align on the hexagonal lattice of h-BN [12]. This epitaxial interaction is schematically presented in Figure 1a by matching the LC benzene rings on the hexagons of the h-BN lattice.…”
Section: Methodsmentioning
confidence: 94%
“…For example, the epitaxial interactions between the nematic LC and the hexagonal lattice of graphene, molybdenum diselenide, and tungsten diselenide deposited [1][2][3][4][5][6][7][8][9][10] demonstrate that the LC can achieve a planar-aligned state on these 2D hexagonal nanostructures. Our group has recently shown that the 2D hexagonal boron nitride (h-BN) film can be successfully employed as a planar-alignment agent as well as an ion-capturing agent in electro-optic LC devices [11][12][13]. Here we report the effects of ultrafine 2D h-BN flakes as a colloidal dopant in a nematic LC.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…On the 2D h-BN crystal, the LC molecules can obtain three degenerate planar orientations separated by 60 degrees due to the three-fold rotational symmetry of the hexagonal structure. It is still possible to achieve uniform planar-alignment in-between two h-BN layers (without any PI) in an LC cell [58]. However, that process requires several steps to align two h-BN layers in the same direction to avoid the degenerate planar orientations in the cell [58].…”
Section: Fabrication Of the 2d H-bn Based Lc Devicementioning
confidence: 99%
“…It is still possible to achieve uniform planar-alignment in-between two h-BN layers (without any PI) in an LC cell [58]. However, that process requires several steps to align two h-BN layers in the same direction to avoid the degenerate planar orientations in the cell [58]. Here, we have used one rubbed PI layer and one h-BN layer in the cell.…”
Section: Fabrication Of the 2d H-bn Based Lc Devicementioning
confidence: 99%